2021
DOI: 10.1242/dev.199866
|View full text |Cite
|
Sign up to set email alerts
|

A stop or go switch: glycogen synthase kinase 3β phosphorylation of the kinesin 1 motor domain at Ser314 halts motility without detaching from microtubules

Abstract: It is more than 25 years since the discovery that kinesin 1 is phosphorylated by several protein kinases. However, fundamental questions still remain as to how specific protein kinase(s) contribute to particular motor functions under physiological conditions. Because, within an whole organism, kinase cascades display considerable crosstalk and play multiple roles in cell homeostasis, deciphering which kinase(s) is/are involved in a particular process has been challenging. Previously, we found that GSK3β plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Phosphotransferase activity regulates motor protein function ( Figure 2 ). For example, the kinase glycogen synthase kinase-3β (GSK3β) phosphorylates KHC to inhibit axonal transport and also phosphorylates KLCs to release cargoes ( 15 , 16 ). Studies using perfusion of kinases and their inhibitors into squid axoplasm showed that the stress-activated protein kinases c-Jun N-terminal kinase 3 (JNK3) and p38 mitogen-activated protein kinase (p38 MAPK) directly phosphorylate KHCs to inhibit anterograde transport ( 17 , 18 ).…”
Section: Regulation Of Axonal Transportmentioning
confidence: 99%
“…Phosphotransferase activity regulates motor protein function ( Figure 2 ). For example, the kinase glycogen synthase kinase-3β (GSK3β) phosphorylates KHC to inhibit axonal transport and also phosphorylates KLCs to release cargoes ( 15 , 16 ). Studies using perfusion of kinases and their inhibitors into squid axoplasm showed that the stress-activated protein kinases c-Jun N-terminal kinase 3 (JNK3) and p38 mitogen-activated protein kinase (p38 MAPK) directly phosphorylate KHCs to inhibit anterograde transport ( 17 , 18 ).…”
Section: Regulation Of Axonal Transportmentioning
confidence: 99%
“…A recent study further suggested that Glycogen Synthase Kinase 3β (GKS3β) could phosphorylate Drosophila KHC at the S314 residue in the α6 helix interfacing the head and the neck-linker domain (Banerjee et al, 2021). The phosphomimetic S314D and the phosphodeficient S314A substitutions severely affected the motor function.…”
Section: Effects Of Kinesin-1 Phosphorylation On Motor Functionmentioning
confidence: 99%
“…Although it did not detach the motor from the microtubule, the ATPase activity and microtubule gliding in vitro were significantly reduced. The mutations also affected the axonal transport of mitochondria in Drosophila (Banerjee et al, 2021). The neck-linker domain moves to a significant extent during the ATPase cycle to generate the force along microtubule during the ATPase cycle (Rice et al, 1999;Vale and Milligan, 2000), which is likely to transiently increase tension on the α6 segment during each stepping cycle (Qin et al, 2020).…”
Section: Effects Of Kinesin-1 Phosphorylation On Motor Functionmentioning
confidence: 99%
“…Phosphorylation of kinesins subunits on different sites by GSK3 can lead to different outcomes. For example, GSK3β phosphorylation of KIF1A at S402 impairs transport but does not regulate mobility, whereas phosphorylation of kinesin-1 motor domain at S314 halts motility without detaching from microtubules ( Gan et al, 2020 ; Banerjee et al, 2021 ). In SH-SY5Y cells and neuronal hippocampal cultures, GSK3 phosphorylation of KLC1 and KLC2 results in decreased association of cargoes from the kinesin cargo system, indicating failed delivery of cargos to their target locations ( Du et al, 2010 ; Morel et al, 2012 ).…”
Section: Direct Substrates Of Gsk3 Regulated By Lithiummentioning
confidence: 99%